ARTIFICIAL INTELLIGENCE (AI) -BASED DIGITAL ADVERTISING ON TIKTOK ON INTEREST CONSUMER BUYING (Study of Undergraduate Students of the Faculty of Social and Political Sciences, Malikussaleh University) - Melda Nilam Sari; Sutriani; Nanda Ameliany; Sufi; Nursakinah Ritonga (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to determine and analyze the effect of Artificial Intelligence (AI)-based digital advertising on TikTok on consumer purchase intention among undergraduate students of the Faculty of Social and Political Sciences, Malikussaleh University. The study employed a quantitative survey approach and simple linear regression analysis. The sample consisted of 100 students selected through purposive sampling with proportional allocation across six study programs. Primary data were collected using a Likert-scale questionnaire and processed with SPSS version 27. The results show that AI-based digital advertising on TikTok has a positive and significant effect on consumer purchase intention. This is proven by a calculated t-value of 11.761, which is greater than the critical t-value of 1.984, with a significance value of 0.000 < 0.05. The correlation coefficient of 0.765 indicates a strong relationship, while the coefficient of determination of 0.585 shows that digital advertising explains 58.5% of the variation in purchase intention. These findings confirm that advertisements that are easy to understand, innovative, persuasive, and entertaining can increase consumers' interest in seeking product information and developing purchase intention